Formation of Ideas About Marriage to Young People - Yuldoshev Tojiddin Abdukarimovich; Urozov Fakhriddin Isokovich; Shomurotov Ulugbek Melikmurodovich (Zien Journals, 2023)
Currently, the number of family conflicts in society is increasing, one of the reasons for this is that young people's ideas about family life are not sufficiently formed. This article describes the problem of psychological preparation of young people for family life. The views of eastern thinkers and modern approaches to the formation of ideas about the family, as well as socio-psychological issues related to the family, were discussed. In this article, we can discuss about the formation of ideas about marriage to young people.
Keywords: ideas; marriage; family; young people